(untitled) - Yapp, Malcolm (London,New York, 1996)
This clear, balanced and authoritative survey of the history of the region is now fully up to date again. The text contains a general regional introduction, followed by a series of country-by-country analyses, and a section which places the Near East in the international context. Professor Yapp' s new edition covers recent dramatic events including the end of the Cold War, the Kuwayt Crisis of 1990/91, and the continuing conflict in Israel, as well as assessing the huge social and economic changes in the region. It will be essential reading for students and scholars concerned with modern middle eastern history and politics of the middle east.
Keywords: Middle East,Trung Đông; History,Lịch sử; 20th century,Thế kỷ 20